HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN FLOW AKADEMIK DENGAN PRESTASI BELAJAR MATEMATIKA SISWA SMA - Putri, Endah Mustikaningsih Rahaju (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
The achievement a student gets in learning mathematics plays on important role as a standard to measure his competence in the subject. The achievement cannot be sparated from influencing factors. This study is meant to reveal the correlation between social support and academic flow with the mathematics learning achievement. This study is a quantitative research whose objects of research are 230 students of ten and eleven year. The sampling technique uses cluster random sampling and data analysis technique using double regression and Pearson correlation . The result of the study shows a positive correlation between social support and academic flow altogether with the mathematics learning achievement (R= 0.178; R Square= 0.032). The result of Pearson correlation test shows a relationship between sosial support and mathematics learning achievement (p= 0.032) except informational and instrumental support aspect. Academic flow has a significant correlation with mathematics learning achievement (p= 0.019) except enjoyment aspect. Thus, it can be concluded that social support (external factor) and academic flow (internal factor) are related to mathematics learning achievement. This shows that internal and external factors in learning process influence the mathematics learning achievements.